Nanostructured composite material graphite/TiO2 and its antibacterial activity under visible light irradiation - Dědková, Kateřina; Lang, Jaroslav; Matějová, Kateřina; Peikertová, Pavlína; Holešinský, Jan; Vodárek, Vlastimil; Kukutschová, Jana (Journal of photochemistry and photobiology. B, Biology, 2015)
The paper addresses laboratory preparation, characterization and in vitro evaluation of antibacterial activity of graphite/TiO2 nanocomposites. Composites graphite/TiO2 with various ratio of TiO2 nanoparticles (30wt.%, and 50wt.%) to graphite were prepared using a thermal hydrolysis of titanylsulfate in the presence of graphite particles, and subsequently dried at 80°C. X-ray powder diffraction, transmission electron microscopy and Raman microspectroscopy served as phase-analytical methods distinguishing anatase and rutile phases in the prepared composites. Scanning and transmission electron microscopy techniques were used for characterization of morphology of the prepared samples. A developed modification of the standard microdilution test was used for in vitro evaluation of daylight induced antibacterial activity, using four common human pathogenic bacterial strains (Staphylococcus aureus, Escherichia coli, Enterococcus faecalis and Pseudomonas aeruginosa). Antibacterial activity of the graphite/TiO2 nanocomposites could be based mainly on photocatalytic reaction with subsequent potential interaction of reactive oxygen species with bacterial cells. During the antibacterial activity experiments, the graphite/TiO2 nanocomposites exhibited antibacterial activity, where differences in the onset of activity and activity against bacterial strains were observed. The highest antibacterial activity evaluated as minimum inhibitory concentration was observed against P. aeruginosa after 180min of irradiation.
Keywords: Nanoparticles; titan; Graphite; antibakteriální látky; světlo; nanočástice; grafit; Titanium; Bacteria; Raman microspectroscopy; lidé; Light; Staphylococcus aureus; Anti-Bacterial Agents; Humans; XRD; Antibacterial activity